POLA PENYEBARAN SEDIMEN TERSUSPENSI BERDASARKAN ANALISIS DEBIT MAKSIMUM DAN MINIMUM DI MUARA SUNGAI PORONG, KABUPATEN PASURUAN - Herna Octivia Damayanti; Undang Hernawan (Pusbindiklat - LIPI, 2014)
Porong estuary is a place where materials transported along the river have been accumulated as well as Sidoarjo sludge. The amount of sediment in the estuary causes high turbidity levels of the river. The objective of this study is to determine the pattern and the concentration of Total Suspended Solid (TSS) spreading in Porong estuary for 15 days with SED2D models from software SMS 8.1 using maximum and minimum riverflow input, thus, the model results that are closer to reality in nature can be obtained. Tides, currents, and TSS were used as primary data sources, while Porong riverflow, Juanda wind and bathymetry maps Java-North Coast Surabaya to Bali Strait scale 1: 200.000 Sheet V No.82 year 2006 as secondary data sources. The results of the research showed that the concentration of TSS spreading for maximum riverflow 248–158 mg/l and minimum riverflow input 248–160 mg/l with spreading pattern tend to go to southeast direction. TSS concentration spreading model verification indicates that the model with the maximum riverflow data input has smaller MRE value than the model with the minimum riverflow.